2023
DOI: 10.3389/fmicb.2023.1098813
|View full text |Cite
|
Sign up to set email alerts
|

Litter size influences rumen microbiota and fermentation efficiency, thus determining host early growth in goats

Abstract: IntroductionMultiple litters are accompanied by low birth weight, low survival rates, and growth rates in goats during early life. Regulating rumen microbiota structure can indirectly or directly affect host metabolism and animal growth. However, the relationship between high litter size and rumen microbiome, rumen fermentation, and growth performance in goat kids is unclear.MethodsIn the present study, thirty 6-month-old, female goats were investigated, of which 10 goats were randomly chosen from single, twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Notably, we found that dietary AO3 supplementation heightened the abundance of f_Prevotellaceae within piglet feces. Prevotellaceae-driven intestinal microbiota has been associated with various animal traits, including feed intake, feed efficiency, weight gain, and diarrhea incidence [53][54][55]. These associations suggest that Prevotella plays a pivotal role in improving growth performance and mitigating intestinal stress and injury caused by LPS challenge upon AO3 supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that dietary AO3 supplementation heightened the abundance of f_Prevotellaceae within piglet feces. Prevotellaceae-driven intestinal microbiota has been associated with various animal traits, including feed intake, feed efficiency, weight gain, and diarrhea incidence [53][54][55]. These associations suggest that Prevotella plays a pivotal role in improving growth performance and mitigating intestinal stress and injury caused by LPS challenge upon AO3 supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…This species has been linked to integral aspects of women’s reproductive health. It has been demonstrated that a reduction in L. jensenii abundance has a close correlation with early-stage embryo arrest [34]. Furthermore, research suggests that L. jensenii may hold potential in facilitating vertical transmission from mother to infant [35].…”
Section: Discussionmentioning
confidence: 99%